تأثير بيئة عمل التمريض على الاحتراق الوظيفي للممرضين في وحدات الرعاية المركّزة - داؤد, نسرين; جردي, منال; قاضون, رشا (Latakia University Journal -Medical Sciences Series, 2017)
لكل مؤسسة صحيّة خصائص تميّزها عن غيرها من المؤسسات الأخرى من حيث أنشطتها وأساليبها الخاصة في العمل، وهي عناصر تمثّل في مجموعها بيئة العمل التي يعمل فيها الممرضون، وقد نالتبيئة عمل التمريضفي الآونة الأخيرة اهتماماً دوليّاً، حيث تم التركيز على أهمية وضرورة تحسين هذه البيئة في المشافي، وذلك لما لها من تأثيرعلى المخرجات المتعلقة بالعمل والأفراد والمؤسسات مثل تغيّب التمريض، وانخفاض مستوى الرضا الوظيفي ودوران التمريض بين الأقسام والاحتراق الوظيفي والنيةلترك المهنة أو مكان العمل، فالتمريض يمثّل جزءاً مهمّاً وعنصراً أساسياً في نظام الرعاية الصحية وبناءً على ذلك يعتبر العمل في بيئة ضاغطة قد يؤثر على الصحة النفسية للممرّض ووصوله لمرحلة الاحتراق الوظيفي. لذا هدفت هذه الدراسة إلى تحديد مدى تأثير بيئة عمل التمريض على الاحتراق الوظيفي للممرضين في وحدات الرعاية المركّزة في مشفى الأسد الجامعي والمشفى الوطني في مدينة اللاذقية، أظهرت نتائج الدراسة أنّ بيئة عمل التمريض كانت بيئة عمل غير ملائمة وذلك من وجهة نظر أكثر من نصف أعضاءالكادر التمريضي المشارك في الدراسة، كما تبيّن أن التواصل والعلاقات بين الأطباء والتمريض برأي الكادر التمريضي من أكثر الأبعاد تحقيقاً في بيئة العمل، تلاه كفاية الموارد والممرضين، ثم القيادة والإشراف التمريضي والدعم من قبل الإدارة، ثم مشاركة التمريض في شؤون المشفى، بينما كان تقدير التمريض والاعتراف بأهمية دوره أقل أبعاد بيئة العمل تحقيقاً برأي المشاركين. كما بيّنت النتائج أيضاً وجود مستوى عالٍ من الاحتراق الوظيفي لدى الكادر التمريضي، ووجود علاقة بين بيئة عمل التمريض وحدوث الاحتراق الوظيفي حيث تأثر الاحتراق الوظيفي بكل أبعاد بيئة عمل التمريض،وكانت ضعف القيادة والإشراف التمريضي والدعم من قبل الإدارة أكثر أبعاد هذه البيئة تأثيراً في حدوث الاحتراق الوظيفي بينما كان التواصل والعلاقات بين الأطباء والتمريض أقل الأبعاد تأثيراً في حدوث الاحتراق الوظيفي.Each health care organisation has certain characteristics in terms of activities and work methods, that differentiate areorganisation from the other. These characteristics represent the work environment that nurses work within. Nursing work environment received an international attention recentlyspecial emphasis on the importance of improvinghospitals environment for its influence on organizational and individuals outcomes such as absence of nurses, job dissatisfaction, nursing turnover , Burnout ,intention to leave the profession workplace, nursing represents an important part of an essential element in the system of health care, work in the pressing environment can affect the psychological health and arrival at Burnout .This study aim to study the impact of nursing work environment on nurse’ burnout in critical care units in government hospital settings in Lattakia. The study showed that the environment of nursing work environment is unfavorable, from the point of view of more than half of the nursing staff participating in the study ,where the highest scoring of subscale was:/nurse physician communications skills/ and lowest scoring of subscale was/nurse foundations for quality of care/ ,well as the study showed the existence of a direct relationship between the work environment unfavorable and burnout , and the work environment in all its dimensions affect the burnout, where after /nurse manager's ability, leadership, and support of nurses/ where the most influential dimensions in the nurse’ burnout, while /nurse-physician communications skills/ the less influential dimensions in the development of nurse’ burnout, on , study showed that there is a link between each of the dimensions of the an environment nursing work and dimensions of the burnout, where that the / nurse foundations for quality of care/ importance of its role more than the impact in raising the rate of emotional exhaustion, while after /nurse participation in organization affairs/ of the importance of its role more than the dimensions of the work environment impact in raising the rate of depersonalization, as it was after the / adequacy of resources and nurses/ more than the dimensions of the work environment impact in reducing the proportion of personal achievement.